ANCHORING AND AFFORESTATION OF DUNE SANDS UNDERLINED WITH SALT SOIL - Sabirov Mirzabay Kabulovich (International Journal on Orange Technologies, 2021)
The article presents the study’s results on the consolidation and afforestation of dune sands underlain by saline soil in Turtkul forestry enterprise desert zone of the Republic of Karakalpakstan and Khorezm forestry enterprise. Experimental work was carried out to consolidate and afforestation the windward dune slopes by installing mechanical protection from reed with planting along them seedlings of black saxaul, Paletsky cherkez. The main goal of the work was to flatten the upper unsecured part of the dune, sand the salt marsh in order to create protective forest cultures from psammophyte shrubs on them